The Influence of Teacher Competence and Differentiated Instruction on the Learning Outcomes of Students with Special Educational Needs: The Mediating Role of Learning Motivation - Qiran; Moh. Marham Mubaraq Lumi; Darman; Muh Rijal (Journal of Educational Technology and Innovation, 2026)
This study examined the influence of teacher competence and differentiated instruction on the learning outcomes of students with special educational needs through the mediating role of learning motivation. The study was motivated by the need to improve the quality of inclusive education through teachers' competence in implementing differentiated learning that accommodates students' diverse characteristics and learning needs. A quantitative approach with an explanatory survey design was employed. The participants consisted of 53 teachers from inclusive schools and special schools selected using purposive sampling. Data were collected through a structured questionnaire distributed via Google Forms and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), supported by Pearson correlation and multiple regression analyses. The findings revealed that differentiated instruction had the strongest positive effect on students' learning outcomes (β = 0.579), followed by learning motivation (β = 0.281). Teacher competence was positively associated with differentiated instruction (r = 0.766) and learning motivation (r = 0.806), indicating that competent teachers were more capable of implementing adaptive instructional strategies that enhanced students' motivation. Furthermore, the proposed structural model demonstrated satisfactory explanatory power, with an R² value of 0.703, indicating that 70.3% of the variance in learning outcomes was explained by teacher competence, differentiated instruction, and learning motivation. The results confirm that learning motivation functions as a mediating variable linking teacher competence and differentiated instruction to students' learning outcomes. These findings highlight the importance of strengthening teacher competence and implementing differentiated instruction to improve learning outcomes in inclusive education.